Method for improving volume expansion effect of silicon-based negative electrode
Through the preparation of graphene-coated silicon material, porous carbon-coated silicon material and electrostatic self-assembly method, the problems of volume expansion and structural failure of silicon-based negative electrode materials are solved, the electrochemical performance and specific capacity of the battery are improved, and the More stable electrode structure.
Patent Information
- Application Number
- CN202411321739.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Silicon-based anode material is structurally damaged due to volume expansion and mechanical stress in lithium-ion batteries, affecting the cycling performance and specific capacity of the battery.
The preparation method of graphene-coated silicon material is prepared by in-situ synthesis method, and the porous carbon-coated silicon material is coated in the graphene sheet layer by electrostatic self-assembly method to improve the conductivity and stability of the composite material. , reduce the impact of volume expansion on the electrode structure.
Effectively suppress the volume expansion of silicon-based materials, improve electrochemical performance and specific capacity, enhance the stability of the electrode structure, reduce the loss of active materials and increase resistance caused by structural damage, and achieve more effective charging and discharging reaction.
Smart Images

Figure BDA0005054165880000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium batteries, in particular to a method for improving the volume expansion effect of a silicon-based negative electrode. Background Art
[0002] Graphite has become the negative electrode active material for most lithium-ion power and energy storage batteries on the market due to its advantages such as a stable discharge platform, high gram capacity, and low price. At present, the reversible specific capacity of graphite negative electrode materials is close to the theoretical specific capacity of 372mA·h / g. In recent years, with the vigorous development of the new energy industry, the demand for high-energy-density lithium-ion batteries has increased. The development of high-specific-capacity negative electrode materials to replace graphite has become an important choice for the research and development of high-energy-density lithium-ion batteries. Silicon negative electrode materials have long been considered as negative electrode active materials for the next generation of high-energy-density lithium-ion batteries due to their high theoretical gram capacity (4200mA·h / g at high temperature and 3590mA·h / g at room temperature), environmental friendliness, and abundant reserves.
[0003] The volume change of silicon during the lithium insertion and extraction process is >300%, accompanied by high mechanical stress, which will cause the active particles to pulverize, thereby destroying the integrity of the electrode structure. At the same time, it will also destroy the SEI film on the silicon surface, causing the exposed silicon surface to directly contact the electrolyte. The repeated growth of the SEI film insulates the pulverized silicon secondary particles and loses electrical contact with the current collector, resulting in a continuous attenuation of silicon lithium storage performance. In addition, silicon is a typical semiconductor material with low intrinsic conductivity (1.56×10 -3 S / m) and a small lithium ion migration coefficient (10 -14 ~10 -13 cm 2 / s), so the rate performance of silicon is poor. In order to solve the problems of expansion and failure of silicon-based materials, the silicon-based negative electrode modification methods currently used in the industry include silicon oxidation, nano-sizing, composite, porosity, alloying, pre-lithiation, etc. Among them, the silicon-carbon composite material obtained by mixing nano-silicon and graphite material has the advantages of good stability, small volume change and excellent conductivity, and is the preparation method with the fastest industrial progress. In the preparation process of silicon-carbon negative electrode, nano-silicon particles are first prepared to make silicon have more gaps to buffer the stress and deformation generated by silicon in the process of lithium ion insertion and extraction. The outermost layer is coated with carbon to form a shell-core structure. At present, the commercial capacity of silicon-carbon negative electrode is below 450mA·h / g, with high first efficiency, but large volume expansion, so its cycle performance is relatively poor. The preparation process of silicon-carbon negative electrode material is relatively complicated, and a standardized preparation method has not yet been formed, and there are certain difficulties in large-scale production.
[0004] In order to overcome the defects of the prior art, the present invention provides a method for improving the volume expansion effect of a silicon-based negative electrode. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the volume expansion effect of a silicon-based negative electrode, so as to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a graphene-coated silicon material comprises the following steps:
[0008] Step 1: Mix liquid trichlorosilane and liquid praseodymium nitrate, and stir them thoroughly at 25-30° C. to obtain a silicon chloride cluster reaction solution;
[0009] Step 2: Heat the silicon chloride cluster reaction solution to 80-90°C, add magnesium powder, and continue stirring to obtain a silicon reaction solution;
[0010] Step 3: introducing argon into the silicon reaction liquid at 700-800°C for 3-5 hours, cooling it to 25-30°C after the insulation, and then washing it with acid and water to obtain a porous carbon-coated silicon material;
[0011] Step 4: Ultrasonic disperse the porous carbon-coated silicon material in the polydiallyldimethylammonium chloride solution, fully stir for 5-7 hours, and then filter, wash, and freeze-dry to obtain a modified porous carbon-coated silicon material; then ultrasonically disperse the modified porous carbon-coated silicon material in deionized water to obtain a reaction solution; add the graphene oxide aqueous solution drop by drop into the reaction solution, and hydrothermally react at 110-130°C for 11-13 hours to obtain a graphene-coated silicon material.
[0012] More optimally, in step 1, the reaction molar ratio of liquid trichlorosilane and liquid praseodymium nitrate is 1:
[0013] (1-1.5).
[0014] More optimally, in step 2, the reaction molar ratio of silicon chloride clusters to magnesium powder is 1:(6-7).
[0015] More optimally, in step 4, the mass concentration of polydiallyldimethylammonium chloride is 0.5-1.5wt%.
[0016] More optimally, in step 4, the concentration of the graphene oxide aqueous solution is 2-4 mg / ml.
[0017] A negative electrode sheet comprises a graphene-coated silicon material as a negative electrode active material, and the negative electrode active material, acetylene black, and polyvinylidene fluoride are dissolved in an N-methylpyrrolidone solvent to obtain a negative electrode slurry; the negative electrode slurry is coated on a surface of a copper foil, and vacuum dried at 120-140° C. for 10-14 hours. After drying, the copper foil is cut into discs with a diameter of 1.4 cm to obtain a negative electrode sheet.
[0018] More optimally, the contents of the components of the negative electrode slurry are: by mass fraction, 75%-85% of the negative electrode active material, 5-15% of acetylene black, and the balance of polyvinylidene fluoride; wherein the loading of the negative electrode active material is 0.5-0.7 mg cm -2 .
[0019] More optimally, in an argon environment, a metal lithium sheet is used as a positive electrode sheet, a polypropylene film is used as a separator, and LiPF6 electrolyte and a negative electrode sheet are assembled to obtain a battery.
[0020] Optimally, the LiPF6 electrolyte concentration is 1-1.2 mol·L -1 The solvent of the electrolyte is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:(1-2); the electrolyte also includes 2-3wt% of the additive vinylene carbonate.
[0021] More optimally, the purity of argon is 99.5-99.9%; the polypropylene film is Celgard2400.
[0022] Beneficial effects of the present invention:
[0023] The present invention firstly prepares a porous carbon-coated silicon material by an in-situ synthesis method, and then prepares the porous carbon-coated silicon material into a graphene-coated silicon material by an electrostatic self-assembly method. The main reaction mechanism is: liquid trichlorosilane undergoes disproportionation in the presence of tertiary amine to produce reactive oligomeric silane chloride, and then uses magnesium powder to reduce the oligomeric silane chloride under mild conditions to generate silicon, and then anneals to obtain the porous carbon-coated silicon material. Then, a positively charged polymer is modified on the surface of the porous carbon-coated silicon material, and the porous carbon-coated silicon material is coated in a graphene sheet with an extremely high elastic modulus by using the negatively charged functional groups on graphene oxide through electrostatic adsorption, thereby improving the conductivity of the composite material, and inhibiting the volume expansion of the porous carbon-coated silicon material, thereby improving the electrochemical performance.
[0024] The present invention can provide additional space for the volume expansion of silicon by introducing porous carbon with a rich pore structure as a component of the silicon-based material, thereby reducing the squeezing and damage to the electrode structure. In addition, the three-dimensional network structure of the porous carbon can disperse the stress throughout the material to avoid structural damage caused by local stress concentration. Similar to a crowded space, the porous structure provides more "channels" and "vacancies" to enable the pressure to be more evenly distributed and released, thereby reducing damage to the electrode material. The reduction in volume expansion helps to maintain the relative stability of the electrode structure during the charge and discharge process. This stability helps to reduce problems such as the loss of active materials and the increase in internal resistance of the electrode due to structural damage, so that the battery can more effectively carry out charge and discharge reactions, give full play to the electrochemical properties of the active materials, and thus improve the specific capacity.
[0025] In addition, the porous carbon introduced in the present invention can also limit the excessive movement and agglomeration of silicon particles to a certain extent. Without the restraint of porous carbon, silicon particles may move and aggregate violently during the volume change process, resulting in instability of the electrode structure and rapid degradation of performance. The pores of porous carbon can "fix" silicon particles, allowing them to move within a certain range, thereby maintaining the relative stability of the electrode structure. In addition, the good conductivity of porous carbon itself also helps to improve the performance of silicon negative electrodes. It can improve the electronic conductivity of the electrode and make charge transfer faster and more efficient, which is helpful to alleviate problems such as increased resistance due to volume expansion to a certain extent, thereby indirectly assisting in suppressing the negative impact of volume expansion on battery performance.
[0026] The present invention is characterized in that:
[0027] 1. The traditional reduction of trichlorosilane, SiCl4 or other tetravalent silicon precursors usually requires highly active sodium naphthalene, Na metal or NaK alloy or higher temperature; while the in-situ synthesis method of the present invention has high repeatability and does not require any sacrificial template. Compared with other preparation methods, the in-situ synthesis method can achieve one-pot synthesis of carbon-coated silicon nanoparticles, showing its advantages.
[0028] 2. The present invention further prepares the porous carbon-coated silicon material into a graphene-coated silicon material, which can effectively improve the conductivity of the composite material and inhibit its volume expansion during the charge and discharge process, thereby improving the electrochemical performance. The main reasons are: ① Graphene has a super elastic modulus (1.1TPa) and fracture strength (125GPa), a high electron mobility (2000cm 2 ·V -1 ·s -1 ) and a high transmittance (95%); ② The low-dimensional structure of graphene can significantly reduce the boundary scattering of phonons at the grain boundaries, giving it excellent thermal conductivity (5300 W·m -1 ·K -1 );③Graphene has a large specific surface area (2630m 2 ·g -1 ), as well as higher chemical and thermal stability. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Source of raw materials:
[0031] Trichlorosilane, provided by Hunan Huibaishi Biotechnology Co., Ltd., model TCl-8472, purity 98%; praseodymium nitrate, provided by Jinan Dehou Chemical Co., Ltd., industrial grade, purity >99%; magnesium powder, provided by Changzhou Meiyao Chemical Co., Ltd., particle size 20-150 mesh; polydiallyldimethylammonium chloride, provided by Yixing Qingtai Purifier Co., Ltd., model CW-41; graphene oxide, provided by Shanghai Maoguo Nanotechnology Co., Ltd., model MG-GO-01, thickness 1nm, single layer diameter 0.5μm; acetylene black, provided by Tianjin Huacai Chemical Co., Ltd., model HCY-80; graphite, provided by Luoyang Tongrun Information Technology Co., Ltd., particle size 5-10μm; copper foil, provided by Shandong Huiya Metal Technology Co., Ltd., T2 copper foil, thickness 8μm; electrolyte, provided by Guangzhou Tianci High-tech Materials Co., Ltd.; polyvinylidene fluoride, provided by Shanghai Qianfu Industrial Co., Ltd., model 761A.
[0032] Example 1: Step 1: Mix liquid trichlorosilane and liquid praseodymium nitrate, and stir them thoroughly at 30° C. to obtain a silicon chloride cluster reaction solution; the reaction molar ratio of the liquid trichlorosilane to the liquid praseodymium nitrate is 1:1;
[0033] Step 2: heating the silicon chloride cluster reaction liquid to 80° C., adding magnesium powder, and continuously stirring to obtain a silicon reaction liquid; the reaction molar ratio of the silicon chloride cluster to the magnesium powder is 1:6;
[0034] Step 3: annealing the silicon reaction solution at 700°C with argon for 4 hours, cooling it to 25°C after annealing, and then acid-washing and water-washing to obtain a porous carbon-coated silicon material;
[0035] Step 4: Ultrasonic dispersion of the porous carbon-coated silicon material in a polydiallyldimethylammonium chloride solution, fully stirring for 6 hours, and then filtering, washing, and freeze-drying to obtain a modified porous carbon-coated silicon material; ultrasonic dispersion of the modified porous carbon-coated silicon material in deionized water to obtain a reaction solution; dropwise addition of a 2 mg / ml graphene oxide aqueous solution into the reaction solution, and hydrothermally reacting at 120° C. for 12 hours to obtain a graphene-coated silicon material; wherein the mass concentration of the polydiallyldimethylammonium chloride is 1 wt%;
[0036] Step 5: Using the graphene-coated silicon material as the negative electrode active material; dissolving 80% of the negative electrode active material, 10% of acetylene black, and 10% of polyvinylidene fluoride in N-methylpyrrolidone solvent by mass fraction to obtain a negative electrode slurry;
[0037] Step 6: Coat the negative electrode slurry on the surface of the copper foil, vacuum dry it at 120°C for 12 hours, and cut it into discs with a diameter of 1.4 cm after drying to obtain the negative electrode sheet; the negative electrode active material loading is 0.5 mg cm-2 ;
[0038] Step 7: Under argon environment, assemble the lithium metal sheet as the positive electrode, the polypropylene film as the separator, the LiPF6 electrolyte, and the negative electrode to obtain a battery; wherein the argon purity is 99.7%; the polypropylene film is Celgard2400; the concentration of LiPF6 electrolyte is 1 mol·L -1 The solvent of the electrolyte consists of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1; the electrolyte also includes 2 wt% of the additive vinylene carbonate.
[0039] Example 2: Step 1: Mix liquid trichlorosilane and liquid praseodymium nitrate, and stir them thoroughly at 30° C. to obtain a silicon chloride cluster reaction solution; the reaction molar ratio of the liquid trichlorosilane to the liquid praseodymium nitrate is 1:1;
[0040] Step 2: heating the silicon chloride cluster reaction liquid to 80° C., adding magnesium powder, and continuously stirring to obtain a silicon reaction liquid; the reaction molar ratio of the silicon chloride cluster to the magnesium powder is 1:6;
[0041] Step 3: annealing the silicon reaction solution at 800°C with argon for 4 hours, cooling it to 25°C after annealing, and then acid-washing and water-washing to obtain a porous carbon-coated silicon material;
[0042] Step 4: Ultrasonic dispersion of the porous carbon-coated silicon material in a polydiallyldimethylammonium chloride solution, fully stirring for 6 hours, and then filtering, washing, and freeze-drying to obtain a modified porous carbon-coated silicon material; ultrasonic dispersion of the modified porous carbon-coated silicon material in deionized water to obtain a reaction solution; dropwise addition of a 2 mg / ml graphene oxide aqueous solution into the reaction solution, and hydrothermally reacting at 120° C. for 12 hours to obtain a graphene-coated silicon material; wherein the mass concentration of the polydiallyldimethylammonium chloride is 1 wt%;
[0043] Step 5: Using the graphene-coated silicon material as the negative electrode active material; dissolving 80% of the negative electrode active material, 10% of acetylene black, and 10% of polyvinylidene fluoride in N-methylpyrrolidone solvent by mass fraction to obtain a negative electrode slurry;
[0044] Step 6: Coat the negative electrode slurry on the surface of the copper foil, vacuum dry it at 120°C for 12 hours, and cut it into discs with a diameter of 1.4 cm after drying to obtain the negative electrode sheet; the negative electrode active material loading is 0.5 mg cm -2 ;
[0045] Step 7: Under argon environment, assemble the lithium metal sheet as the positive electrode, the polypropylene film as the separator, the LiPF6 electrolyte, and the negative electrode to obtain a battery; wherein the argon purity is 99.7%; the polypropylene film is Celgard2400; the concentration of LiPF6 electrolyte is 1 mol·L -1 The solvent of the electrolyte consists of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1; the electrolyte also includes 2 wt% of the additive vinylene carbonate.
[0046] Comparative Example 1: A porous carbon-coated silicon material was used as a negative electrode active material, and an argon gas was introduced at 800° C. for 4 h to prepare a porous carbon-coated silicon material. The rest was the same as in Example 1, and the specific steps were as follows: Step 1: Liquid trichlorosilane and liquid praseodymium nitrate were mixed, and stirred for reaction at 30° C. to obtain a silicon chloride cluster reaction solution; the reaction molar ratio of the liquid trichlorosilane and the liquid praseodymium nitrate was 1:1;
[0047] Step 2: heating the silicon chloride cluster reaction liquid to 80° C., adding magnesium powder, and continuously stirring to obtain a silicon reaction liquid; the reaction molar ratio of the silicon chloride cluster to the magnesium powder is 1:6;
[0048] Step 3: annealing the silicon reaction solution at 800°C with argon for 4 hours, cooling it to 25°C after annealing, and then acid-washing and water-washing to obtain a porous carbon-coated silicon material;
[0049] Step 4: Using porous carbon-coated silicon material as negative electrode active material; dissolving 80% of negative electrode active material, 10% of acetylene black, and 10% of polyvinylidene fluoride in N-methylpyrrolidone solvent by mass fraction to obtain negative electrode slurry;
[0050] Step 5: Coat the negative electrode slurry on the surface of the copper foil, vacuum dry it at 120°C for 12 hours, and cut it into discs with a diameter of 1.4 cm after drying to obtain the negative electrode sheet; the negative electrode active material loading is 0.5 mg cm -2 ;
[0051] Step 6: Under argon environment, assemble the lithium metal sheet as the positive electrode, the polypropylene film as the separator, the LiPF6 electrolyte, and the negative electrode to obtain a battery; wherein the argon purity is 99.7%; the polypropylene film is Celgard2400; the concentration of LiPF6 electrolyte is 1 mol·L -1 The solvent of the electrolyte consists of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1; the electrolyte also includes 2 wt% of the additive vinylene carbonate.
[0052] Comparative Example 2: A porous carbon-coated silicon material was used as a negative electrode active material, and an argon gas was introduced at 700° C. for 4 h to prepare the porous carbon-coated silicon material. The rest was the same as in Example 1, and the specific steps were as follows: Step 1: Liquid trichlorosilane and liquid praseodymium nitrate were mixed, and the mixture was stirred and reacted at 30° C. to obtain a silicon chloride cluster reaction solution; the reaction molar ratio of the liquid trichlorosilane and the liquid praseodymium nitrate was 1:1;
[0053] Step 2: heating the silicon chloride cluster reaction liquid to 80° C., adding magnesium powder, and continuously stirring to obtain a silicon reaction liquid; the reaction molar ratio of the silicon chloride cluster to the magnesium powder is 1:6;
[0054] Step 3: annealing the silicon reaction solution at 700°C with argon for 4 hours, cooling it to 25°C after annealing, and then acid-washing and water-washing to obtain a porous carbon-coated silicon material;
[0055] Step 4: Using porous carbon-coated silicon material as negative electrode active material; dissolving 80% of negative electrode active material, 10% of acetylene black, and 10% of polyvinylidene fluoride in N-methylpyrrolidone solvent by mass fraction to obtain negative electrode slurry;
[0056] Step 5: Coat the negative electrode slurry on the surface of the copper foil, vacuum dry it at 120°C for 12 hours, and cut it into discs with a diameter of 1.4 cm after drying to obtain the negative electrode sheet; the negative electrode active material loading is 0.5 mg cm -2 ;
[0057] Step 6: Under argon environment, assemble the lithium metal sheet as the positive electrode, the polypropylene film as the separator, the LiPF6 electrolyte, and the negative electrode to obtain a battery; wherein the argon purity is 99.7%; the polypropylene film is Celgard2400; the concentration of LiPF6 electrolyte is 1 mol·L -1 The solvent of the electrolyte consists of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1; the electrolyte also includes 2 wt% of the additive vinylene carbonate.
[0058] Comparative Example 3: A porous carbon-coated silicon material was used as a negative electrode active material, and an argon gas was introduced at 700° C. for 8 h to prepare the porous carbon-coated silicon material. The rest was the same as in Example 1, and the specific steps were as follows: Step 1: Liquid trichlorosilane and liquid praseodymium nitrate were mixed, and the mixture was stirred and reacted at 30° C. to obtain a silicon chloride cluster reaction solution; the reaction molar ratio of the liquid trichlorosilane and the liquid praseodymium nitrate was 1:1;
[0059] Step 2: heating the silicon chloride cluster reaction liquid to 80° C., adding magnesium powder, and continuously stirring to obtain a silicon reaction liquid; the reaction molar ratio of the silicon chloride cluster to the magnesium powder is 1:6;
[0060] Step 3: annealing the silicon reaction solution at 700°C with argon for 8 hours, cooling it to 25°C after annealing, and then acid-washing and water-washing to obtain a porous carbon-coated silicon material;
[0061] Step 4: Using porous carbon-coated silicon material as negative electrode active material; dissolving 80% of negative electrode active material, 10% of acetylene black, and 10% of polyvinylidene fluoride in N-methylpyrrolidone solvent by mass fraction to obtain negative electrode slurry;
[0062] Step 5: Coat the negative electrode slurry on the surface of the copper foil, vacuum dry it at 120°C for 12 hours, and cut it into discs with a diameter of 1.4 cm after drying to obtain the negative electrode sheet; the negative electrode active material loading is 0.5 mg cm -2 ;
[0063] Step 6: In an argon environment, a lithium metal sheet is used as a positive electrode sheet, a polypropylene film is used as a separator, and a LiPF6 electrolyte and a negative electrode sheet are assembled to obtain a battery; wherein the purity of the argon is 99.7%; the polypropylene film is Celgard2400; the concentration of the LiPF6 electrolyte is 1 mol·L -1 The solvent of the electrolyte consists of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1; the electrolyte also includes 2 wt% of the additive vinylene carbonate.
[0064] Detection test:
[0065] Specific capacity test: The batteries prepared in Examples 1-2 and Comparative Examples 1-3 were tested using CT2001A 5V / 1mA test equipment. The test mode was set to constant current charge and discharge test. The battery was charged and discharged at a current density of 0.1A / g and a voltage range of 2.0 to 3.65V, and then the specific capacity was calculated as battery capacity / main material load. The above steps were repeated according to the settings to test and calculate the specific capacity at current densities of 0.2, 0.5, 1, 2, and 5A / g. The results are shown in the following table:
[0066]
[0067] Conclusion: The results show that with the increase of current density, the discharge capacity value gradually decreases. At different current densities, the specific capacity of the battery prepared in the embodiment is better than that of the battery prepared in the comparative example. Specifically, at a current density of 2.0 A / g, the specific capacities of Example 1 (graphene-coated silicon material, annealed at 700°C with argon for 4 h) and Example 2 (graphene-coated silicon material, annealed at 800°C with argon for 4 h) are 14 The specific capacities of comparative example 2 (using porous carbon-coated silicon material and annealing at 700°C with argon for 4h) and comparative example 1 (using porous carbon-coated silicon material and annealing at 800°C with argon for 4h) are 1102mA·h / g and 1256mA·h / g respectively; the specific capacity of comparative example 3 (using porous carbon-coated silicon material and annealing at 700°C with argon for 8h) is 1188mA·h / g.
[0068] From the analysis data, it can be seen that the present invention can provide additional space for the volume expansion of silicon by introducing porous carbon with rich pore structure as a component of silicon-based materials, thereby reducing the squeezing and damage to the electrode structure. In addition, the three-dimensional network structure of porous carbon can also disperse stress throughout the material to avoid structural damage caused by local stress concentration. The above performance improvements help to maintain the relative stability of the electrode structure during the charge and discharge process. This stability helps to reduce problems such as loss of active materials and increase in internal resistance of the electrode due to structural damage, so that the battery can more effectively carry out charge and discharge reactions, give full play to the electrochemical properties of active materials, and thus improve the specific capacity. For silicon negative electrodes, the volume expansion is more serious during the charge and discharge process. Therefore, by introducing the porous carbon with rich pore structure prepared by the present invention as a component of silicon-based materials, the volume expansion can be reduced, thereby better playing the advantages of high specific capacity materials such as silicon negative electrodes, and then improving the overall specific capacity of the battery, as shown in the example data.
[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0070] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a graphene-coated silicon material, characterized in that: The following steps are involved: Step 1: Mix liquid trichlorosilane and liquid praseodymium nitrate, and stir them thoroughly at 25-30° C. to obtain a silicon chloride cluster reaction solution; Step 2: Heat the silicon chloride cluster reaction solution to 80-90°C, add magnesium powder, and continue stirring to obtain a silicon reaction solution; Step 3: introducing argon into the silicon reaction liquid at 700-800°C for 3-5 hours, cooling it to 25-30°C after the insulation, and then washing it with acid and water to obtain a porous carbon-coated silicon material; Step 4: Ultrasonic disperse the porous carbon-coated silicon material in the polydiallyldimethylammonium chloride solution, fully stir for 5-7 hours, and then filter, wash, and freeze-dry to obtain a modified porous carbon-coated silicon material; then ultrasonically disperse the modified porous carbon-coated silicon material in deionized water to obtain a reaction solution; add the graphene oxide aqueous solution drop by drop into the reaction solution, and hydrothermally react at 110-130°C for 11-13 hours to obtain a graphene-coated silicon material.
2. The method for preparing a graphene-coated silicon material according to claim 1, characterized in that: In step 1, the reaction molar ratio of liquid trichlorosilane to liquid praseodymium nitrate is 1:(1-1.5).
3. The method for preparing a graphene-coated silicon material according to claim 1, characterized in that: In step 2, the reaction molar ratio of silicon chloride clusters to magnesium powder is 1:(6-7).
4. The method for preparing a graphene-coated silicon material according to claim 1, characterized in that: In step 4, the mass concentration of polydiallyldimethylammonium chloride is 0.5-1.5wt%.
5. The method for preparing a graphene-coated silicon material according to claim 1, characterized in that: In step 4, the concentration of the graphene oxide aqueous solution is 2-4 mg / ml.
6. A negative electrode plate, characterized in that: The graphene-coated silicon material is used as the negative electrode active material, and the negative electrode active material, acetylene black, and polyvinylidene fluoride are dissolved in N-methylpyrrolidone solvent to obtain a negative electrode slurry; the negative electrode slurry is coated on the surface of the copper foil, and vacuum dried at 120-140° C. for 10-14 hours to obtain a negative electrode sheet.
7. A negative electrode sheet according to claim 6, characterized in that: The content of each component of the negative electrode slurry is: by mass fraction, 75%-85% of negative electrode active material, 5-15% of acetylene black, and the balance is polyvinylidene fluoride; the loading of the negative electrode active material is 0.5-0.7 mg cm -2 .
8. A method for improving the volume expansion effect of a silicon-based negative electrode, characterized in that: A negative electrode sheet as described in any one of claims 6 to 7 is used.
9. The method for improving the volume expansion effect of a silicon-based negative electrode according to claim 8, characterized in that: In an argon environment, a metal lithium sheet is used as a positive electrode sheet, a polypropylene film is used as a separator, and LiPF6 electrolyte and a negative electrode sheet are assembled to obtain a battery.
10. The method for improving the volume expansion effect of a silicon-based negative electrode according to claim 8, characterized in that: The concentration of LiPF6 electrolyte is 1-1.2 mol·L -1 The solvent of the electrolyte is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:(1-2); the electrolyte also includes 2-3wt% of the additive vinylene carbonate.
Citation Information
Patent Citations
High-performance porous film silicon-based negative electrode material of lithium ion cell and preparation method thereof
CN102683656A
Silicon-carbon negative electrode material and preparation method thereof
CN106920949A
Preparation method of double-layer carbon modified silicon negative electrode material
CN115440969A
Preparation method of silicon-carbon composite lithium ion battery negative electrode material
CN117542993A
Cited By
Silicon negative electrode plate, preparation method thereof and lithium ion battery
CN120356902A
Silicon-carbon negative electrode material and preparation method and application thereof
CN122233356A